1992
DOI: 10.1002/app.1992.070450315
|View full text |Cite
|
Sign up to set email alerts
|

A molecular model for solid‐state polymerization of nylon 6

Abstract: SYNOPSISA theoretical model is developed for the effect of segmental diffusion on reversible step growth polymerization. This model is a n adaptation of the molecular model of Chiu et al. for characterizing the Trommsdorff effect in free-radical polymerization. The model is applied to the specific case of solid-state polymerization of spherical pellets of nylon 6. The results of the simulation are found to show qualitative trends as found by Gaymans et al. experimentally. The parameters of the model are curve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 19 publications
1
28
0
2
Order By: Relevance
“…Using the same physical picture as that of CCS the authors [175] finally came to the following equation relating the polycondensation rate coefficient to the diffusivity of the polymer molecules, D and the effective diffusion radius, r m :…”
Section: Solid State Polycondensation Of Polyamidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same physical picture as that of CCS the authors [175] finally came to the following equation relating the polycondensation rate coefficient to the diffusivity of the polymer molecules, D and the effective diffusion radius, r m :…”
Section: Solid State Polycondensation Of Polyamidesmentioning
confidence: 99%
“…[175][176][177][178][179] Kaushik and Gupta [175] presented a theoretical model for the effect of segmental diffusion on the SSP of Nylon 6. The following kinetic scheme was supposed:…”
Section: Solid State Polycondensation Of Polyamidesmentioning
confidence: 99%
“…Satisfactory agreement between theory and experimental data was observed. The sensitivity of the results to the parameters is studied by Gupta [18] with the value of 1 from 10 À1 to 10 À5 , the value of 2 from 2000 to 10.…”
Section: Methodsmentioning
confidence: 99%
“…For values of W s above 10 À2 mol/kg, however, the results were sensitive to its value. Kaushik and Gupta [18] studied the effect of W s on the SSP process. It was found that the increase of molecular weight is insensitive when the value of W s is below 10 À4 mol/kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation